A Tissue-Specific Rhythmic Recruitment Pattern of Leukocyte Subsets - Yuan, Yinglin; Wu, Shengwang; Li, Weiwei; He, Wenyan (Frontiers in Immunology, 2020)
The leukocytes circulating in the vasculature to reach various organs is a crucial step to perform their function. With a sequence of interaction with the endothelial cells, the leukocytes emigrate from the circulation either by firm attachment to vascular beds or trafficking into the tissues. Recent findings reveal that the leukocytes recruitment shows time as well as tissue specificity depending on the cell type and homing location. This spatiotemporal distribution of leukocyte subsets is driven by the circadian expression of pro-migratory molecules expressed on the leukocytes and the endothelium. Both the systemic circadian signals and the cell intrinsic molecule clock contribute to the oscillatory expression of pro-migratory molecules. The rhythmic recruitment of leukocytes plays an important role in the time-dependency of immune responses. It also helps to update blood components and maintain the tissue circadian microenvironment. In this review, we discuss the current knowledge about the mechanisms of the circadian system regulating the leukocyte rhythmic migration, the recruitment pattern of leukocyte subsets into different tissue/organs, and the time-dependent effects behind this process.